2017
DOI: 10.1080/07315724.2017.1318317
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Red and Processed Meat Intake and Markers of Adiposity and Inflammation: The Multiethnic Cohort Study

Abstract: Objective The potential influence of dietary factors on inflammation is important for cancer prevention. Utilizing data from control participants (312 men, 911 women) in two nested case-control studies of cancer within the Multiethnic Cohort, we examined the associations of red and processed meat intake with serum levels of leptin, adiponectin, C-reactive protein (CRP), tumor necrosis factor (TNF)-α, and interleukin (IL)-6 and the mediator effect of body mass index (BMI) on the above associations (if present).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
55
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(63 citation statements)
references
References 30 publications
(40 reference statements)
6
55
0
2
Order By: Relevance
“…We did not find any significant associations of unprocessed red meat with CRP, triglycerides, or HDL cholesterol in never smokers or current smokers. The null results among never smokers are partially supported by some previous studies, in which investigators demonstrated null associations between red meat and CRP after the adjustment of BMI 23,24 in the general healthy population; however, they did not conduct further stratified analyses based on smoking status. A recent meta-analysis indirectly supported our finding on lipids that the consumption of red meat did not change blood lipid levels in healthy individuals.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…We did not find any significant associations of unprocessed red meat with CRP, triglycerides, or HDL cholesterol in never smokers or current smokers. The null results among never smokers are partially supported by some previous studies, in which investigators demonstrated null associations between red meat and CRP after the adjustment of BMI 23,24 in the general healthy population; however, they did not conduct further stratified analyses based on smoking status. A recent meta-analysis indirectly supported our finding on lipids that the consumption of red meat did not change blood lipid levels in healthy individuals.…”
Section: Discussionmentioning
confidence: 68%
“…Previous studies examined whether red meat intake was associated with increased inflammation and disturbed blood lipids; however, the results were not consistent. Some studies found that the associations between red meat and C‐reactive protein (CRP), the most commonly used marker of inflammation, were largely attenuated and no longer significant after adjustment of the body mass index . A recent meta‐analysis summarising intervention studies showed that red meat intakes do not change blood lipid levels .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, animal proteins, especially red meat are introduced as risk factors of diabetes progression [10,11]. Although underlying mechanisms which associate red meat consumption with its progressive metabolic abnormalities are not well defined, it is suggested that obesity-related inflammation and insulin resistance may be involved to some extent [12,13] Also red meat contains high saturated fat which could be related to hyperinsulinemia and risk of type 2 diabetes [14]. Based on previous clinical trials, the effect of red meat and plantbased proteins on diabetes outcomes is still controversial [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%